Implementasi Program Kampus Mengajar Di Sekolah Menengah Kejuruan Negeri 5 Palangka Raya - Pasaribu, Aldo Radot Hamonangan Pasaribu; T.Tamba, Josua Fransiskus Tamba; Lisa Virgiyanti; Junisen Rolexlin Sirat; Nia Febriani; Alifah Lutfiana; Rolita Grace Cyndi Purba; Sri Rahmawati; Bell Petter Simandalahi; Frans Nathanael Manurung; Vincend Tiovan Manurung; Pujihastuty; Bukhari, Noormalina Martina (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2025)
SMKN-5 Palangka Raya has high dedication in improving the quality of education and developing student competencies. The Teaching Campus Program exists as an effort to support students in the learning process while facilitating their adaptation to technological developments. The main objective of the Batch 1 Teaching Campus Program is to provide support to teachers and staff in developing potential and improving school quality. This program includes counseling and training on the use of technology, such as teaching students about Word software, as well as teaching and coaching activities aimed at strengthening students' character. In addition, this program prioritizes cooperation to improve school quality and deepen understanding between students. The method applied in the Teaching Campus Program uses a qualitative approach. Various achievements that have been achieved during the implementation of the Batch 1 Teaching Campus Program include the creation of a reading corner, provision of toga plant racks, repair of school name signs and updating of writing in schools, implementation of literacy and numeracy activities, construction of rubbish bins, renewal of ceremonial equipment, as well as routine ceremonial training on Mondays and holidays. Apart from that, the activities carried out also included cleaning and painting the pool behind the school, making shelves for family medicinal plants, as well as training on the use of Microsoft Excel and Word to improve students' basic technology skills.